How healthy are Manitoba’s Francophones? A summary of report, Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Ottawa, Manitoba Center for Health Policy, 2012)
A summary of the report, Health and Healthcare Utilization of Francophones in Manitoba / La santé et l’utilisation des services de santé des francophones du Manitoba by Mariette Chartier, Greg Finlayson, Heather Prior, Kari-Lynne McGowan, Hui Chen, Janelle de Rocquigny, Randy Walld, Michael Gousseau Summary written by Michelle Houlden

Quel est l’état de santé des francophones du Manitoba ? Sommaire du rapport intitulé La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, University of Manitoba, 2012)

Une innovation réussie et durable au sein d’un réseau de santé, soit un hôpital et centre de santé communautaire en région rurale au Canada - Collin, Stéphanie; Michaud, Nancy; Ringuette, Claudie (Revue francophone sur la santé et les territoires, 2024)
Dans le monde, les décideurs publics tentent de trouver des arrangements structuraux pour améliorer la performance des systèmes de santé. La stratégie de régionalisation a été privilégiée depuis quelques décennies par une majorité des provinces canadiennes. Dans cet article, nous nous penchons sur les dynamiques relationnelles entre les acteurs associés à une régie régionale de la santé et leur influence sur la naissance et l’adoption d’une pratique innovante, soit un hôpital et centre de santé communautaire en région rurale. Une méthode de recherche qualitative a été retenue et la collecte de données a été effectuée par le biais d’entretiens semi-dirigés, de groupes de discussion, ainsi qu’une analyse documentaire. L’émergence et la pérennité d’une pratique innovante nécessitent une définition de la santé qui fait consensus, la présence d’entrepreneurs institutionnels et une redéfinition des rôles et responsabilités entre l’autorité centrale et les acteurs locaux. La mise en œuvre d’une gouvernance collaborative est également requise.

Évaluation de l’offre active des services de santé de première ligne - Comité santé en français de Fredericton (Groupe Progecom communication et stratégies d’entreprise, 2006)

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Regards sur la société canadienne, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Insights on Canadian Society, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Systematic Search and Evaluation of mobile Apps for Wound Care Available in French-Language in Canada - Gagnon, Julie; Chartrand, Julie; Probst, Sebastian; Maillet, Éric; Reynolds, Emily; Chaplain, Valérie; St-Jean, Heidi; East, Raphaelle; Lalonde, Michelle (Canadian Journal of Nursing Research, 2025)
Background Wounds are a significant national health concern, impacting individuals, healthcare systems, and the environment. Despite efforts by organizations to promote evidence-based practices, gaps persist between theory and nurse practice in wound care. Mobile apps show promises in enhancing wound care delivery, but their rapid evolution, including adaptations into different languages such as French, raises concerns about reliability and regulation. Evaluating these apps is crucial for ensuring patient safety and effective wound management. Purpose To review and assess mobile wound care apps available in French for healthcare providers in Canada. Methods A systematic search was conducted across the literature and the two main Canadian online app stores (App Store and Google Play). The included mobile apps underwent quality evaluation using the user version of the Mobile Application Rating Scale (uMARS). Results The initial search retrieved 1,550 apps, of which 260 were screened and 5 included. Included apps were from France and were available on both stores. These apps varied in features, including wound dressing directory ( n = 3), best practices reminders ( n = 2), photography management and digital wound tracking ( n = 1), and total body surface area calculator ( n = 1). Evaluation using uMARS indicated total averages range from 3.52/5 to 4.10/5. The results offer scant insight into the design and evaluation of the apps included. Conclusions The study highlights the need for development and validation of a French wound care app tailored to Canadian healthcare contexts and best practice recommendations, emphasizing collaboration among nurses and stakeholders in technology enhancement for the benefit of Canadians’ health.

Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)

Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

Improving the recruitment and retention of doctors by training medical students locally - Landry, Michel; Schofield, Aurel; Bordage, Rachel; Bélanger, Mathieu (Medical Education, 2011)
Context The global shortage of doctors is of concern. This is particularly true in French‐speaking regions of New Brunswick, Canada, where there is no medical school. Since 1981, francophone medical students from New Brunswick have been able to undertake part of their training in their province through an agreement with medical schools in another province. We studied the effects of frequency and length of exposure to the province of origin during medical training on the likelihood that a doctor will ever or currently practise medicine in that province. Methods A questionnaire was sent to 390 francophone doctors from New Brunswick to collect information on history of medical training and practice. Multivariate logistic regressions were used to identify whether exposure to New Brunswick during medical training at the undergraduate and postgraduate levels affects the likelihood of ever or currently practising in the province. Results A total of 263 doctors participated. Among family doctors, those with exposure to their province of origin in 1, 2, 3 or 4 years of undergraduate training were 2.5 (95% confidence interval [CI] 0.8–7.4), 2.5 (95% CI 0.7–8.6), 9.3 (95% CI 1.5–56.9) and 9.3 (95% CI 1.4–60.1) times more likely, respectively, to currently practise in New Brunswick than doctors who had experienced no exposure to the province during undergraduate training. Among specialty doctors, exposure to New Brunswick during undergraduate training had no effect on location of practice. Family and specialty doctors who had been exposed to New Brunswick during postgraduate residency were 5.9 (95% CI 2.3–14.9) and 3.2 (95% CI 0.9–11.6) times more likely, respectively, to practise in the province than doctors without postgraduate exposure. Conclusions Greater exposure to New Brunswick during medical training is associated with significantly better odds that doctors will be recruited to and retained in the province. Some effects are perceived for exposure during both undergraduate (most importantly in the final years) and postgraduate programmes.

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)

Impact de la crise de la COVID-19 sur les familles francophones dans les Prairies canadiennes - Leis, Anne; De Moissac, Danielle; Proulx-Cullen, Elyse; Gnidehou, Sedami; Marchak, Kristan A.; Keough, Catelyn; Chaput, Mélanie; Turgeon, Marianne (Minorités linguistiques et société, 2025)
Contexte et but. Dans le contexte linguistique minoritaire où l’accès à des services en français est un défi, l’étude voulait documenter dans quelle mesure la crise de la pandémie avait eu un impact sur les familles francophones au Manitoba, Saskatchewan et Alberta. Méthodes. À partir des informations recueillies lors de 6 World Café du Monde, un sondage a été créé et distribué en ligne aux membres d’organismes francophones dans ces provinces. Des analyses descriptives et de régression ont été menées. Résultats. Des 319 familles, la grande majorité a reconnu l’impact négatif et anxiogène de la pandémie. Plusieurs facteurs de risque ont été identifiés : une compréhension moyenne ou faible de l’anglais, la déconnexion avec la communauté francophone locale, la difficulté de vivre en français en famille et de suivre la scolarité de ses enfants à la maison. Conclusion. La pandémie a été un défi pour les familles francophones des Prairies. Des ressources accrues en français et des politiques de soutien sont recommandées. , Background and aim. Within the linguistic minority context where access to services in French is a challenge, the study aimed to document to what extent the pandemic had an impact on Francophone families in Manitoba, Saskatchewan and Alberta. Methods. Based on the qualitative analysis of data collected in 6 World Cafés, an on-line survey was distributed to members of Francophone organizations in these provinces. Descriptive and regression analyses were conducted. Results. Of 319 families, the majority recognized the negative and anxiety provoking aspects of the pandemic. Several risk factors were identified: an average or below average mastery of English, isolation from the local Francophone community, difficulty with living in French with their family and supporting children’s education at home. Conclusion. The pandemic was a challenge for Francophone families in the Prairies. Additional resources in French and supportive policies are recommended.

Language as a barrier to care for Xhosa-speaking patients at a South African paediatric teaching hospital - Levin, M. E. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Disease is closely linked to the social context in which we live. Difficulty with communication, cultural incompatibility between patients and health care providers and socioeconomic obstacles are important barriers to quality care when doctors and patients come from different backgrounds and speak different languages. Red Cross War Memorial Children's Hospital (RCH) is a paediatric teaching hospital in Cape Town where staff members communicate mainly in English or Afrikaans, while many patients speak Xhosa as their first language. OBJECTIVES: The study aimed to identify barriers to optimal care for Xhosa-speaking parents of patients at RCH. The contribution of language difficulties was assessed as a possible barrier to health care for this group. DESIGN: A questionnaire was developed and administered to 53 Xhosa-speaking parents of children admitted to the short-stay ward at RCH. The questionnaire examined parents' perceptions of barriers to their children's care, using openended questions, closed-ended questions and selection from lists. RESULTS: Parents experienced significant structural and socioeconomic barriers to access of health care for their children. Language and cultural barriers were cited by more parents as a major barrier to health care than structural and socioeconomic barriers. Parents did not have access to same-language practitioners, as only 6% of medical interviews were conducted partly or wholly in the patient's home language. Of the 94% of interviews where no Xhosa was spoken by medical staff, 21% were conducted with the aid of an interpreter (formal or ad hoc) and in 79% no interpreter was used. Parents experienced difficulties with understanding the doctors (64%), making themselves understood (54%) and asking questions (38%). Sixty-nine per cent of parents were dissatisfied with communication between themselves and their doctors and 45% were concerned about negative effects of poor communication on them or their children. Parents tended to blame their own linguistic limitation rather than those of the doctors.
Keywords: Adolescent; Adult; Communication Barriers; Cultural Characteristics; Health Care Surveys; Health Services Accessibility; Hospitals, Pediatric; Hospitals, Teaching; Humans; Language; Middle Aged; Multilingualism; South Africa

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Le présent rapport et l’Enquête sur la population de langue officielle en situation minoritaire de 2022 ont bénéficié du soutien financier et de la collaboration soutenue du ministère du Patrimoine canadien. Cette étude a pu être réalisée grâce au travail de longue haleine de plusieurs équipes et personnes qui se sont relayées au fil des ans pour planifier, concevoir, préparer, tester, réaliser, assurer la qualité des données, documenter, analyser et diffuser cette enquête d’envergure. Les auteurs tiennent à remercier toutes les personnes qui ont participé à ce processus, en particulier, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑ Hélène Toupin, Danielle Léger et Catherine Dufour. Plusieurs autres membres du personnel actuel ou passé de Statistique Canada ont contribué de manière importante à cette enquête au fil du temps, dont Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean‑Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu et Dominique Pérusse, de même que les équipes internes des activités de collecte et de traitement des données. Pour leur soutien, leurs conseils et leur aide à la production du rapport, merci à Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini et Pierre‑France Bondesen‑David. Soulignons également l’expertise et l’orientation fournies par les réviseurs ainsi que les membres du comité de direction et les membres du comité scientifique de l’enquête.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
This report and the 2022 Survey on the Official Language Minority Population received funding and ongoing support from the Department of Canadian Heritage. This study was made possible thanks to the tireless efforts of many different teams and individuals who, over the years, contributed to planning, designing, preparing, testing, conducting, ensuring data quality, documenting, analyzing and publishing this major survey. The authors would like to thank each and every one of them, especially, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑Hélène Toupin, Danielle Léger and Catherine Dufour. Many other current or former Statistics Canada staff members have made, over the years, important contributions to this survey including Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu and Dominique Pérusse, as well as the in‑house data collection and processing teams. For their support, advice and help in producing the report, thanks to Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini and Pierre‑France Bondesen‑David. We would also like to acknowledge the expertise and guidance of the editors, as well as the members of the Interdepartmental Steering Committee and the survey Scientific Committee.

Final Report – Improving the Francophone Experience in Healthcare - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

Rapport final – Amélioration de l’expérience des francophones dans les soins de santé - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

Argumentaire pour la promotion d’une offre de service santé de qualité dans la langue maternelle des clients au Nunavut - Réseau Santé en français au Nunavut (2021)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

À la rencontre des communautés acadiennes et francophones et de leurs enjeux en santé - Réseau Santé Nouvelle Écosse (Réseau santé en français de Nouvelle-Écosse, 2021)

Report on the 2020–2023 Café de Paris Manitoba Pilot Project - Roberge, Jérémie (Santé en français Manitoba, 2023)

Pratique # 4 : L’intégration de la variable linguistique dans la collecte de données (Île-du-PrinceÉdouard) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)